2023
DOI: 10.3389/fneur.2022.1030940
|View full text |Cite
|
Sign up to set email alerts
|

Neuroepidemiology study of headache in the region of Jammu of north Indian population: A cross-sectional study

Abstract: BackgroundHeadache disorders now represent a major public health problem globally. It is more prevalent in developing countries with the rising trends of headache disorders observed in young adults affecting their quality of life negatively. Very little information is available on the epidemiology of headache disorders in the Jammu Division of the north Indian population.AimThe aim of the present study was to find out the prevalence of headache and its two major types, i.e., migraine and tension-type headache … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Using the same, multiple research studies have been conducted over the previous two decades; however, contradictory results have been discovered (Table 1), which might be related to demographic diversifcation, ethnic diversity, and varied sample size. But, in the recent polled analysis, a nonsignifcant association was observed with overall migraine but critical increases in the Asian ethnic group [50]. We cannot ignore the fndings from the genomewide association study (GWAS), which identifed several infammatory genes such as TSPAN2, MEF2D, NLRP1, JAM3, and NOTCH4, but the TNF-α was not replicated [51].…”
Section: Tnf-α In Association Withmentioning
confidence: 96%
See 1 more Smart Citation
“…Using the same, multiple research studies have been conducted over the previous two decades; however, contradictory results have been discovered (Table 1), which might be related to demographic diversifcation, ethnic diversity, and varied sample size. But, in the recent polled analysis, a nonsignifcant association was observed with overall migraine but critical increases in the Asian ethnic group [50]. We cannot ignore the fndings from the genomewide association study (GWAS), which identifed several infammatory genes such as TSPAN2, MEF2D, NLRP1, JAM3, and NOTCH4, but the TNF-α was not replicated [51].…”
Section: Tnf-α In Association Withmentioning
confidence: 96%
“…Since then, the definition has expanded dramatically and is now defined as “a brain condition featured with low neuronal hyperexcitability and vascular dysfunction as a consequence leading to the unwanted severe head pain (the cardinal feature)” [ 1 ]. Regarding its prevalence and disability, the Global Burden Disorder-2019 (GBD-2019) has enlightened that the general prevalence is about 24% (GBD 2019) with a variation related to the gender difference with the majority of females than males [ 2 , 3 ]. This gender prevalence diversity is mainly due to hormonal differences.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the advanced GWAS, numerous independent studies have been carried out in various populations and have identified various genes that are responsible for disease risk attribution. Using India as an example of a population, which is part of the Asian ethnic group where migraine disorder is very common 8 12 , many genes have been studied (Table 1 ) but the association between these genes and migraine risk has been found to be inconsistent 13 36 .…”
Section: Introductionmentioning
confidence: 99%
“…One such example is migraine, which is defined as a complex, polygenic/ multifactorial, dysautonomic, common, and chronic neurovascular disorder featuring unilateral head pain [4]. It is responsible for high disability-adjusted life years (DALYs), an overall high prevalence (15.75%) (Healthdata.org) with varied prevalence rates between sexes i.e., the female occurrence is more (12-17%) than male prevalence [5,6]. Migraine patients have significantly higher visits to healthcare providers, and diagnose the condition according to the ICHD-3 are unilateral headache, vomiting, phono-phobia, photophobia, and some patient also experiences stomach and abdominal pain, dizziness, pale skin color, and tiredness.…”
Section: Introductionmentioning
confidence: 99%